2002
DOI: 10.2172/15001167
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vadose Zone Sediment: Borehole 299-W23-19 [SX -115] in the S-SX Waste Management Area.

Abstract: Executive SummaryThis report was revised in September 2008 to remove acid-extractable sodium data from Tables 4.15 and 4.19. The sodium data was removed due to potential contamination introduced during the acid extraction process. The rest of the text remains unchanged from the original report issued in February 2002.The Tank Farm Vadose Zone Project is led by CH2M HILL Hanford Group, Inc. Their goals include defining risks from past and future single-shell tank farm activities, identifying and evaluating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(92 citation statements)
references
References 13 publications
10
75
7
Order By: Relevance
“…If the absolute concentrations of co-migrating species are changed solely by dilution with existing porewater, then the ratio of the two should remain constant. Unlike similar ratio discussions for other contaminated boreholes (SX-41-09-39 and 299-W23-19; see Serne et al 2002b and2002d), the ratios for the porewaters from borehole 299-E33-46 are not constant. It is likely that the low absolute concentrations of constituents such as technetium-99 and relatively low concentrations of nitrate and uranium cause the ratio approach to be compromised by analytical error.…”
Section: Other Characterization Observationscontrasting
confidence: 64%
See 1 more Smart Citation
“…If the absolute concentrations of co-migrating species are changed solely by dilution with existing porewater, then the ratio of the two should remain constant. Unlike similar ratio discussions for other contaminated boreholes (SX-41-09-39 and 299-W23-19; see Serne et al 2002b and2002d), the ratios for the porewaters from borehole 299-E33-46 are not constant. It is likely that the low absolute concentrations of constituents such as technetium-99 and relatively low concentrations of nitrate and uranium cause the ratio approach to be compromised by analytical error.…”
Section: Other Characterization Observationscontrasting
confidence: 64%
“…This differs from the cation profile from borehole 299-W23-19 that shows very distinct separation of the divalent cations from the sodium plume (see Figure 4.4 in Serne et al 2002b) or the less pronounced but still discernable separation from the sodium profile at the two more saline plumes between SX-108 and SX-109 tanks (see Figures 4.3 in both Serne et al 2002c and2002d). Based on personal communication with Dr. Carl Steefel at Lawrence Livermore National Laboratory, the ion exchange separation of the divalent cations, which are naturally the dominant cations on Hanford sediment exchange sites, from the invading high sodium fluids is maximized when the invading sodium concentrations are not large and when the ion exchange capacity of the sediments is moderate.…”
Section: 13contrasting
confidence: 61%
“…Sediment pH values are considered slightly elevated between 8.0 and 8.5 and are significantly elevated above 8.5. Previous characterization activities have shown that soil pH is typically significantly elevated in locations where tank waste has entered the vadose zone (Serne et al 2002b(Serne et al ,c, 2004aBrown et al 2006Brown et al , 2007. Natural minerals in the sediment eventually buffer the alkaline waste solution as it migrates through the vadose zone, resulting in normal soil pH values down gradient from waste source discharge points.…”
Section: Ph and Electrical Conductivitymentioning
confidence: 99%
“…During a past investigation at WMA SX, investigators reported that changes in sediment type and contaminant concentrations typically occurred within a few inches in a given liner (Serne et al 2002b). It was concluded that a more methodical scoping approach would be necessary to provide the technical justification for selecting samples for detailed characterization as defined in the data quality objectives process (DOE 1999).…”
Section: Approachmentioning
confidence: 99%
“…In those instances, it was assumed that recharge through the coarse, nonvegetated tank farm surfaces was large enough for an amount of time sufficient to have flushed the tank leak liquids to a depth in the soil profile that would allow use of the shallower chloride data. Serne et al (2002aSerne et al ( , 2002b reported data for two boreholes inside WMA S-SX, 299-W23-19 and 299-W23-234. Borehole 299-W23-19 is in the southwestern corner of the WMA S-SX, approximately 3 m (10 ft) southwest of SST SX-115, which was confirmed to have leaked in 1965.…”
Section: B33 Deeply Disturbed Sedimentmentioning
confidence: 99%